THE EFFECTIVENESS OF THE TRILATERAL COOPERATIVE ARRANGEMENT (TCA) IN COUNTERING MARITIME TERRORISM BY ABU SAYYAF IN THE SULU SEA - Shabirah, Sarah; Putri, Amarsya Anggita; Oktavianto, Fajar (Department of International Relations Universitas Satya Negara Indonesia, 2026)
This study aims to analyze the effectiveness of the Trilateral Cooperative Arrangement (TCA) in addressing maritime terrorism in the Sulu Sea during the 2016–2020 period. The TCA was implemented through the Trilateral Maritime Patrol (TMP), Trilateral Air Patrol (TAP), and Maritime Command Center (MCC). The study employs a qualitative approach through literature review and secondary data analysis. The findings indicate that the TCA was effective in significantly reducing the intensity of attacks through coordinated patrols, intelligence sharing, and an integrated command system. This is reflected in the 94.4 percent decrease in incidents during the research period. Nevertheless, the effectiveness of the arrangement still faces challenges, including jurisdictional limitations, technological disparities, and dependence on the political commitment of each participating country. This study emphasizes that the sustainability and strengthening of multilateral cooperation are essential to building stable and sustainable regional maritime security.